PENGARUH GAYA KEPEMIMPINAN TERHADAP SEMANGAT KERJA PNS PADA KEMENTERIAN AGAMA KABUPATEN BOGOR - Priatna, Angka; Ferdiansyah, Fariz (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2015)
ABSTRACTOne important element of leadership in relation to the morale is leadership style. Leadership style is the way a leader influences the behavior of subordinates, to cooperate and work productively to achieve organizational goals. High moral can be seen from the amount of presence, good cooperation and harmonious relationship. The analytical method used is the analysis of Spearman Rank correlation coefficient, Coefficient of Determination Analysis and Hypothesis Testing Correlation Coefficient. Based on the calculation of Spearman rank correlation coefficient 0.867 results obtained these figures show that the leadership style has a very strong relationship with moral in the Ministry of Religion Bogor Regency. The coefficient of determination based on the calculation results obtained 75.16%, which means that the leadership style can affect moral downs and the remaining 24.84% influenced by other factors. Calculated based on the hypothesis test, t-test (12.03) > t-table (1.2996), then reject Ho and accept Ha so that there is a positive relationship between leadership style with morale.Keywords: Delegation of Authority, Responsibility, Presence, Cooperation, Harmonious Relationships